Super-chondritic Sm/Nd ratios in Mars, the Earth and the Moon. - Caro, G; Bourdon, B; Halliday, A; Quitté, G (2008)
Small isotopic differences in the atomic abundance of neodymium-142 (142Nd) in silicate rocks represent the time-averaged effect of decay of formerly live samarium-146 (146Sm) and provide constraints on the timescales and mechanisms by which planetary mantles first differentiated. This chronology, however, assumes that the composition of the total planet is identical to that of primitive undifferentiated meteorites called chondrites. The difference in the 142Nd/144Nd ratio between chondrites and terrestrial samples may therefore indicate very early isolation (<30 Myr from the formation of the Solar System) of the upper mantle or a slightly non-chondritic bulk Earth composition. Here we present high-precision 142Nd data for 16 martian meteorites and show that Mars also has a non-chondritic composition. Meteorites belonging to the shergottite subgroup define a planetary isochron yielding an age of differentiation of 40 +/- 18 Myr for the martian mantle. This isochron does not pass through the chondritic reference value (100 x epsilon(142)Nd = -21 +/- 3; 147Sm/144Nd = 0.1966). The Earth, Moon and Mars all seem to have accreted in a portion of the inner Solar System with approximately 5 per cent higher Sm/Nd ratios than material accreted in the asteroid belt. Such chemical heterogeneities may have arisen from sorting of nebular solids or from impact erosion of crustal reservoirs in planetary precursors. The 143Nd composition of the primitive mantle so defined by 142Nd is strikingly similar to the putative endmember component 'FOZO' characterized by high 3He/4He ratios.